Perlindungan Hukum Terhadap Perempuan Dan Anak Korban Tindak Pidana Perdagangan Orang - Ahmad Syaufi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
The protection provided by state law against women and children as victims of the crime of trafficking in persons scattered in several laws and regulations either general or specific nature, such as: Criminal Law, Criminal Procedure Code, Law No.21 of 2007 on Combating Criminal Acts trafficking in Persons, Law No.13 of 2006 on Protection of Witnesses and Victims. It is still not supported by the implementing regulation (Government Regulation) with regard to the mechanism of compensation or restitution which is a form of direct protection to the victim.